ORAL HEALTH AS A MAJOR RISK FACTOR FOR RESPIRATORY INFECTIONS - Tudor Cojocaru; Giulia Mihaela Pînzariu; Ion Andrei Hurjui; Ruxandra Maria Hurjui; Irina Luciana Gurzu (Romanian Society of Oral Rehabilitation, 2023)
One of the leading causes of death worldwide is represented by the respiratory diseases, which include disorders such as pneumonia, occupational lung diseases, asthma, and chronic obstructive pulmonary disease. Recent published data indicate that, in the European Union in 2017, the disorders of the respiratory system were responsible for almost 8% of all deaths [1]. Pulmonary infections could be caused by the oral colonization of possible respiratory pathogens, a process that can be promoted by the specific bacterial flora of the oral cavity or by periodontal diseases.